Changing-look Active Galactic Nuclei: A Study of Optical/UV and the Highly Ionized Fe Kα X-Ray Line Flux Variations Using Photoionization Simulations - Tek P. Adhikari; Santanu Mondal; Zhicheng He; Agata Rozanska; Krzysztof Hryniewicz (The Astrophysical Journal)
Significant variability in broad emission line strengths of active galactic nuclei (AGN) over months to years has been observed, often accompanied by intrinsic continuum changes. Such spectral variability challenges the traditional AGN classification scheme, which attributes differences between type 1 and type 2 to geometrical effects, as transitions between these types occur on timescales shorter than viscous ones. In this work, using the cloudy photoionization simulations, we investigated the response of the major emission line fluxes, in the optical/UV and hard X-ray bands, to changes in the intensity and shape of the continuum emission of the AGN under two scenarios: (i) changes in the X-ray power law while keeping disk emission fixed, and (ii) broadband continuum variations. We demonstrate that broad-line region (BLR) line fluxes are insensitive to X-ray power-law changes alone. Considering a well-studied case of the changing-look (CL) AGN Mrk 1018, which exhibits variations in the intrinsic disk emission, as well as the X-ray power law, our simulations reproduce observed brightening and dimming trends of the BLR emission. Moreover, we show that the highly ionized Fe K α X-ray flux, primarily produced by the H-like and He-like ions of Fe, strongly depends on the X-ray strength of the intrinsic spectral energy distribution. These findings suggest that the origin of highly ionized Fe K α emission is in the coronal part of the accretion disk and that the CL phenomenon can be triggered by intrinsic changes in the accretion properties of AGN.